2013
DOI: 10.2174/0929866511320070006
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Lectin with Antiphytovirus Activities from the wild Mushroom Paxillus involutus

Abstract: A novel lectin was isolated from the dried fruiting bodies of the wild mushroom Paxillus involutus. Isolation was conducted by anion exchange chromatography on DEAE-Cellulose, Q-Sepharose and gel filtration on Superdex 75 using a fast protein liquid chromatography (FPLC) system. This lectin had a molecular mass of 28 kDa and was composed of four identical subunits, each with a molecular mass of 7 kDa. N-terminal amino acid sequence of the P. involutus lectin was determined to be CTCAVFLNNTTVKS, which showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 34 publications
1
9
0
4
Order By: Relevance
“…The lectin from Grifola frondosa is reported to be cytotoxic against HeLa cells at the lectin concentration of 25 μg/mL [ 184 ]. The antiproliferative activity of lectins has also been demonstrated in other mushroom species including Paxillus involutus [ 185 ], Lactarius flavidulus [ 106 ], Hericium erinaceus [ 94 ], Russula delica [ 154 ], Pholiota adiposa [ 133 ], and Clitocybe nebularis [ 79 ], and we have recently shown that the GlcNAc-specific lectin from Psathyrella asperospora (PAL) possess a potent antiproliferative activity (IC 50 : 0.48 μM) [ 186 ]. Further characterization of PAL’s anti-proliferative activity showed that HT29 cells are arrested at G2/M phase of the cell cycle, and that this effect can be halted through the addition of free GlcNAc.…”
Section: Biological Activity Of Mushroom Lectinsmentioning
confidence: 99%
“…The lectin from Grifola frondosa is reported to be cytotoxic against HeLa cells at the lectin concentration of 25 μg/mL [ 184 ]. The antiproliferative activity of lectins has also been demonstrated in other mushroom species including Paxillus involutus [ 185 ], Lactarius flavidulus [ 106 ], Hericium erinaceus [ 94 ], Russula delica [ 154 ], Pholiota adiposa [ 133 ], and Clitocybe nebularis [ 79 ], and we have recently shown that the GlcNAc-specific lectin from Psathyrella asperospora (PAL) possess a potent antiproliferative activity (IC 50 : 0.48 μM) [ 186 ]. Further characterization of PAL’s anti-proliferative activity showed that HT29 cells are arrested at G2/M phase of the cell cycle, and that this effect can be halted through the addition of free GlcNAc.…”
Section: Biological Activity Of Mushroom Lectinsmentioning
confidence: 99%
“…Por otro lado, se evidenció que con el método TCA -acetona -fenol, las manchas se concentran principalmente en el rango de pesos moleculares entre 26,9 y 113,2 kDa, lo cual coincide con lo encontrado previamente usando 1DE y confirma la extracción diferencial de proteínas durante la aplicación de los dos métodos evaluados. De acuerdo con los diversos reportes que se tienen hasta la fecha, en estos rangos de pesos moleculares, se presentan proteínas de origen fúngico que pueden presentar actividad biológica de particular interés para la comunidad científica [13,[61][62][63][64][65]. Este es el caso de una lectina con dos subunidades homólogas de 32 kDa aislada de Pholiota adiposa, la cual presentó capacidad de hemaglutinación y efecto antiproliferativo de las líneas tumorales HepG2 y MCF, así como inhibición de la transcriptasa reversa de la línea VIH-1 [13].…”
Section: Referenciasunclassified
“…Este es el caso de una lectina con dos subunidades homólogas de 32 kDa aislada de Pholiota adiposa, la cual presentó capacidad de hemaglutinación y efecto antiproliferativo de las líneas tumorales HepG2 y MCF, así como inhibición de la transcriptasa reversa de la línea VIH-1 [13]. En la seta Paxillus involutus se encontró, igualmente, una lectina tetramérica de 28 kDa con estabilidad de hemaglutinación [62], la cual adicionalmente presenta actividad anti-fitoviral contra el virus del mosaico del tabaco -TMV. También, se han reportado glicoproteínas en Hypsizygus marmoreus, conformadas por 10 subunidades cada una de 52 kDa (522 kDa en peso molecular total), las cuales demostraron capacidad para la inhibición del crecimiento de la línea celular de leucemia U937 [63] o la presencia de la glicoproteina GFG-3a de 88 kDa, obtenida de Grifola frondosa, la cual induce a la apoptosis en la línea celular de cáncer gástrico SGC-7901 y muestra, además, arresto del ciclo celular en la fase S [64,65].…”
Section: Referenciasunclassified
“…involutus has been reported to exhibit anti-proliferative activity by a 28kDa lectin (Wang et al, 2013). The methodology for genetic identification of Paxillus obscurisporus using ITS2 and NLB4 primers was described in section 2.1.3 of Chapter 2.…”
Section: A Summary Of Biological Activity Exhibited By Mushroom In Thmentioning
confidence: 99%
“…The 5% NaOH extract from Paxillus obscurisporus possessed moderate antiproliferative and strong immuno-stimulatory activities, which made it a favorable extract for further studies. Also, Paxillus obscurisporus is related to Paxillus involutus, which is reported to possess an anti-proliferative lectin with a molecular mass of 24 kDa against lung cancer cells (A-549) and human colon cancer cells (HCT-8) (Wang et al, 2013). Although the extracts from Trichaptum abietinum and Gyromitra esculenta exhibited strong bio-activities, they were not selected for further purification.…”
Section: Selection Of Paxillus Obscurisporus For Purification Of Antimentioning
confidence: 99%